Oceanic oxygenation events in the anoxic Ediacaran ocean. Issue 5 (30th March 2016) - Sahoo, S. K.; Planavsky, N. J.; Jiang, G.; Kendall, B.; Owens, J. D.; Wang, X.; Shi, X.; Anbar, A. D.; Lyons, T. W.
Abstract: The ocean‐atmosphere system is typically envisioned to have gone through a unidirectional oxygenation with significant oxygen increases in the earliest (ca. 635 Ma), middle (ca. 580 Ma), or late (ca. 560 Ma) Ediacaran Period. However, temporally discontinuous geochemical data and the patchy metazoan fossil record have been inadequate to chart the details of Ediacaran ocean oxygenation, raising fundamental debates about the timing of ocean oxygenation, its purported unidirectional rise, and its causal relationship, if any, with the evolution of early animal life. To better understand the Ediacaran ocean redox evolution, we have conducted a multi‐proxy paleoredox study of a relatively continuous, deep‐water section in South China that was paleogeographically connected with the open ocean. Iron speciation and pyrite morphology indicate locally euxinic (anoxic and sulfidic) environments throughout the Ediacaran in this section. In the same rocks, redox sensitive element enrichments and sulfur isotope data provide evidence for multiple oceanic oxygenation events (OOEs) in a predominantly anoxic global Ediacaran–early Cambrian ocean. This dynamic redox landscape contrasts with a recent view of a redox‐static Ediacaran ocean without significant change in oxygen content. The duration of the Ediacaran OOEs may be comparable to those of the oceanic anoxic events (OAEs) in otherwise well‐oxygenated Phanerozoic oceans. Anoxic events caused mass extinctions followed by fast recovery in biologically diversified Phanerozoic oceans. In contrast, oxygenation events in otherwise ecologically monotonous anoxic Ediacaran–early Cambrian oceans may have stimulated biotic innovations followed by prolonged evolutionary stasis.